Inhabiting La Patria : Identity, Agency, and Antojo in the Work of Julia Alvarez - Hipchen, Emily, 1964-; Harrison, Rebecca L., 1970- (Book collections on Project MUSE., 2013)
"Provides insightful criticism from many perspectives and grants in-depth analyses of both well-known and lesser studied texts"--Provided by publisher